E-Cadherin Expression as a Prognostic Factor in Transitional Cell Carcinoma of the Bladder After Transurethral Resection - Khorrami, Mohammad Hatef; Hadi, Mazaher; Gharaati, Mohammad Reza; Izadpanahi, Mohammad Hossein; Javid, Amir; Zargham, Mahtab (Urology Journal, 2012)
PURPOSE: To analyze the role of negative versus positive immunoexpression of E-cadherin in recurrence rate of low-grade bladder tumors. MATERIALS AND METHODS: A total of 180 patients with unifocal, superficial, low-grade, papillary transitional cell carcinoma of the bladder were included in this study. The E-cadherin expression was evaluated using E-cadherin antibody. The patients were followed up for 36 months. Thereafter, recurrence rate of the tumor was compared between E-cadherin positive and negative groups. RESULTS: Of 180 low-grade carcinomas, E-cadherin immunoexpression was negative in 101 (56%) and positive in 79 (44%) patients. The recurrence rate in negative and positive groups was 65.6% and 37.9%, respectively. Negative in comparison with positive E-cadherin expression was associated with more disease recurrence (P = .045). CONCLUSION: There is an association between decreased E-Cadherin immunoexpression and tumor recurrence in low-grade and non-muscle invasive transitional cell carcinoma of the bladder.